2007
DOI: 10.1002/pmic.200700072
|View full text |Cite
|
Sign up to set email alerts
|

The expression of S100A8 in pancreatic cancer‐associated monocytes is associated with the Smad4 status of pancreatic cancer cells

Abstract: The cross-talk between tumour cells and the surrounding supporting host cells (stroma) is a key regulator of cancer growth and progression. By undertaking 2-DE analysis of laser capture microdissected malignant and stromal components of pancreatic tumours and benign ductal elements, we have identified high levels of S100A8 and S100A9 in tumour-associated stroma but not in benign or malignant epithelia. Immunohistochemical analysis (n = 71 patients) revealed strong expression of both proteins in stromal myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 42 publications
6
44
0
Order By: Relevance
“…One recent report found that S100A8 secreted by a distant primary tumor could attract Mac 1(+)-myeloid cells to the premetastatic lung, suggesting that S100A8 plays a role in long distance metastasis (40). Another study found that up-regulation of S100A8 could be detected only in tumor-associated stroma and not in malignant epithelia (41). These findings suggest that up-regulation of immune response genes in TFs could provide a suitable microenvironment for tumor cells.…”
Section: Discussionmentioning
confidence: 94%
“…One recent report found that S100A8 secreted by a distant primary tumor could attract Mac 1(+)-myeloid cells to the premetastatic lung, suggesting that S100A8 plays a role in long distance metastasis (40). Another study found that up-regulation of S100A8 could be detected only in tumor-associated stroma and not in malignant epithelia (41). These findings suggest that up-regulation of immune response genes in TFs could provide a suitable microenvironment for tumor cells.…”
Section: Discussionmentioning
confidence: 94%
“…However, in Smad4-negative tumors, the recruited myeloid cells express S100A9, but exhibit lower S100A8 expression [37], as it occurs in acute inflammatory reactions [38]. In SLE PBMCs the S100A9:A8 ratio was significantly higher than that in Normal PBMCs (Fig.…”
Section: Identification Of a Pattern Of Differentially Expressed Protmentioning
confidence: 99%
“…Immunoprecipitated proteins were separated by 2-D gel electrophoresis as described earlier (Shekouh et al, 2003;Sheikh et al, 2007). Gel images were captured on a GS-800 gel scanner (BioRad, Hertfordshire, UK) and analysed using Progenesis software (NonLinear Dynamics, Newcastle upon Tyne, UK).…”
Section: Two-dimensional Gel Electrophoresis and Protein Identificationmentioning
confidence: 99%
“…Gel images were captured on a GS-800 gel scanner (BioRad, Hertfordshire, UK) and analysed using Progenesis software (NonLinear Dynamics, Newcastle upon Tyne, UK). Protein spots were excised, destained, trypsin digested and subjected to MALDI-TOF MS and/or LC-MS/MS as described earlier (Shekouh et al, 2003;Sheikh et al, 2007). Data were again submitted to Mascot and the NCBI database searched with the MS tolerance set to 1.2 Da and the MS/MS tolerance to 0.6 Da, with carbamidomethyl as a fixed modification.…”
Section: Two-dimensional Gel Electrophoresis and Protein Identificationmentioning
confidence: 99%